The Problems of Online Learning: The Role of Parents During The Covid-19 Pandemic - Akhmad Halim Ilmanto; Eni Fariyatul Fahyuni; Arman Harahap (Nazhruna: Jurnal Pendidikan Islam, 2021)
The COVID-19 pandemic has made very significant changes in the world, changing all aspects of life, one of which is the education sector which makes the emergence of new policies to become school from home (SFH) or all forms of learning are carried out online. problems of parents in dealing with distance or online learning. This research uses a case study approach, the main subjects are parents of Muhammadiyah schools around Sidoarjo. Data collection methods used are google form questionnaires and interviews/interviews. The results of the study indicate that there are problems faced by parents: parents' difficulties in accompanying their children while studying, limited network quotas, tend to be difficult to the condition when learning at home, the content of material taught online or online may not necessarily be understood by all students. The data analysis technique in this study uses data analysis techniques developed by Miles, & Huberman, namely data analysis techniques using interactive analysis with three activity flows, namely data reduction, data presentation, and drawing conclusions.